Maximizing the quality of education by measuring the educational added value in secondary school technical type on the basis of exam results - Polcyn Jan; Czyżewski Bazyli (Management, 2016)
The rationale for this study is the search for ways to optimize expenditures on secondary vocational education. Optimization activities should lead to the creation of high quality human capital in the society.